Enriched Differentiation of Human Otic Sensory Progenitor Cells Derived From Induced Pluripotent Stem Cells - Lahlou, Hanae; Nivet, Emmanuel; Lopez-Juarez, Alejandra; Fontbonne, Arnaud; Assou, Said; Zine, Azel (Frontiers in Molecular Neuroscience, 2018)
Age-related neurosensory deficit of the inner ear is mostly due to a loss of hair cells (HCs). Development of stem cell-based therapy requires a better understanding of factors and signals that drive stem cells into otic sensory progenitor cells (OSPCs) to replace lost HCs. Human induced pluripotent stem cells (hiPSCs) theoretically represent an unlimited supply for the generation of human OSPCs in vitro. In this study, we developed a monolayer-based differentiation system to generate an enriched population of OSPCs via a stepwise differentiation of hiPSCs. Gene and protein expression analyses revealed the efficient induction of a comprehensive panel of otic/placodal and late otic markers over the course of the differentiation. Furthermore, whole transcriptome analysis confirmed a developmental path of OSPC differentiation from hiPSCs. We found that modulation of WNT and TGF signaling combined with FGF3 and FGF10 treatment over a 6-day period drives the expression of early otic/placodal markers followed by late otic sensory markers within 13 days, indicative of a differentiation into embryonic-like HCs. In summary, we report a rapid and efficient strategy to generate an enriched population of OSPCs from hiPSCs, thereby establishing the value of this approach for disease modeling and cell-based therapies of the inner ear.